Addressing Educational Accountability and Political Legitimacy with Citizen Responsibility. Issue 5 (October 2015) - Stitzlein, Sarah M.
Abstract In this essay, Sarah Stitzlein addresses a key current crisis in public education: accountability. Rather than centrally being about poor performance of teachers or inefficiency of schools, as we most often hear in media outlets and in education reform speeches, Stitzlein argues the crisis is at heart one about citizen responsibility and political legitimacy. She claims that the recent accountability movement has shifted the onus of curing society's problems almost exclusively onto schools, but contends that these burdens should not just be unidirectional. There is, Stitzlein maintains, a corresponding obligation on the part of citizens to public schools. This includes all citizens, not just those closely tied to schools through their children or employment. Moreover, this obligation entails a robust commitment that extends beyond merely supporting public schools through taxes, voting for levies, and choosing to send one's children to them. The responsibility of citizens includes upholding a commitment to schools as a central institution of democracy — something that sustains democracy but also, in its best forms, is democracy in action.